Scientific and Practical Conference «Innovations in Neurosurgery», October 14-15, 2014, Kiev - —, — (Ukrainian Neurosurgical Journal, 2014)
The scientific congress V Jubilee International Medical Forum "Innovation in Medicine - Health of the Nation "on October 14-15, 2014 inKieva scientific conference "Innovations in Neurosurgery." The organizers of the conference were the Romodanov Neurosurgery Institute and the Ukrainian Association of Neurosurgeons. The conference discussed the following areas: 1. Neuromodulation 2. Endoscopic techniques in neurosurgery 3. Radioneurosurgery 4. Neuronavigation 5. The newest technologies in neurorehabilitation 6. New technologies in spine surgery 7. Innovative technologies in the diagnosis and treatment in neurologia and neurosurgery. The conference was attended by 77 experts.